Optimum inspection interval for tanker in unified inspection regime - Grbić, Luka; Čulin, Jelena; Hess, Mirano; Hess, Svjetlana (Transport, 2020)
Inspections on board tankers contribute to the prevention of accidents, which can have a significant impact to humans and environment. Therefore a high amount of tanker inspections is performed by various stakeholders. This practice could be made more efficient by introducing unified inspection regime, which covers existing areas of inspection, eliminates overlapping and has the potential to improve safety. In this paper an important aspect in defining inspection regime, inspection interval, is determined considering contradictory goals: lowering the costs of inspection and increasing useful service life of tanker structure and equipment, without compromising safety. A probabilistic approach has been applied to establish inspection schedule, which fulfils a range of requirements. Due to the many varieties of tanker types, their conditions, range of size and age span, the paper focuses on the 10 years AFRAMAX tanker. Results indicate that optimal inspection interval in the unified inspection regime for that tanker should be 3 months. Using modified input parameters, similar approach could be used for other tanker types.